Effect of Grape Pomace Powder Addition on TBARS and Color of Cooked Pork Sausages during Storage - Ryu, Kyeong Seon; Shim, Kwan Seob; Shin, Daekeun (Korean journal for food science of animal resources, 2014)
To determine the effects of grape skin and seed pomace (GSP) additions on the lipid oxidation susceptibility and the color change of cooked pork sausages, the chemical characteristics of GSP itself and the addition for two different levels of GSP (0.5 and 1.0% GSP, respectively) to sausages were examined. Both the redness and blueness of the GSP were significantly reduced as the pH level was increased from 5 to 7, but a reverse result was determined in the color tint and yellowness (p<0.05). The GSP polyphenol and flavonoid contents were influenced by the percentages of methanol solvents, and more flavonoids were established when 100% of methanol was applied as a solvent to the GSP. But, similar results were not observed in the polyphenol of GSP. In cooked pork sausages, significant decreases in the lightness and redness were found in both the 0.5% and 1.0% of GSP sausages during the storage period (p<0.05). However, an incompatible effect was observed in terms of yellowness, which increased as compared to the control sausage after 6 days of storage. The 0.5% addition of GSP decreased the levels of TBARS (p<0.05), but the ability of GSP to minimize lipid oxidation was not dose dependent. Therefore, the results indicated that the GSP is an efficient suppressor of lipid oxidation and has latent effects as a natural antioxidant when 0.5% of GSP is added to the cooked pork sausages.